Expression of B-Cell Lymphoma Protein-2 (Bcl-2) and Caspase-3 are Related with Ovarian Cancer - Budiana, I Nyoman G. (Indonesian Socety of Obstetrics and Gynecology, 2014)
Objective: To determine the expression of Bcl-2 and caspase-3 and their relationship with ovarian cancer. Method: This study was a cross-sectional study. Speciment was tissue sample from ovarian cancer patients collected from parafinblock to determine the Bcl-2 and caspase-3 expression and demographic data obtained secondary from patients medical records. Expression of Bcl-2 and caspase-3 was examined by immunohistochemistry under light microscope with 400x light power field. The result was recorded as negative when the protein was expressed in 10% or less of cells and as a positive when the protein was expressed in more than 10% of cells. Result: A total of 45 samples was included as research subjects. 31 of 45 subjects showed the expression of Bcl-2 positive (68.9%), while the positive expression of caspase-3 was presented in 20 subjects (44.4%). There was a relationship between the expression of Bcl-2 with the expression of caspase-3 in ovarian cancer patients (p=0.002; Lambda=0.4). There was also a negative relationship, where the subjects with positive expression of Bcl-2 showed negative expression of caspase-3. In contrast, subjects with negative expression of Bcl-2 showed positive expression of caspase-3. Conclusion: There was a significance relationship between the expression of Bcl-2 with the expression of caspase-3 in ovarian cancer patients. [Indones J Obstet Gynecol 2014; 2-1: 33-39] Keywords: Bcl-2 expression, caspase-3 expression, ovarian cancer